2012
DOI: 10.6009/jjrt.2012_jsrt_68.4.404
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality Evaluation of New Image Reconstruction Methods Applying the Iterative Reconstruction

Abstract: The purpose of this study was to evaluate the image quality of an iterative reconstruction method, the iterative reconstruction in image space (IRIS), which was implemented in a 128-slices multi-detector computed tomography system (MDCT), Siemens Somatom Definition Flash (Definition). We evaluated image noise by standard deviation (SD) as many researchers did before, and in addition, we measured modulation transfer function (MTF), noise power spectrum (NPS), and perceptual low-contrast detectability using a wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Some previous study reported that the iterative reconstruction algorithm significantly reduced image noise and yielded a higher contrast-to-noise ratio of coronary artery [22,23] . Takata et al [24] also demonstrated that the iterative reconstruction algorithm had the noise reduction performance with exact preservation for high contrast resolution and slight degradation of middle contrast resolution. However, generally noise properties and in-plane spatial resolutions have a trade-off relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous study reported that the iterative reconstruction algorithm significantly reduced image noise and yielded a higher contrast-to-noise ratio of coronary artery [22,23] . Takata et al [24] also demonstrated that the iterative reconstruction algorithm had the noise reduction performance with exact preservation for high contrast resolution and slight degradation of middle contrast resolution. However, generally noise properties and in-plane spatial resolutions have a trade-off relationship.…”
Section: Discussionmentioning
confidence: 99%